Characterization of seismic wave velocity and attenuation and interpretation of tetrahydrofuran hydrate-bearing sand using resonant column testing. (December 2020) - Liu, Zhichao; Ning, Fulong; Hu, Gaowei; Liu, Lele; Liu, Changling; Peng, Li; Wang, Dongdong; Hu, Wei; Zhang, Zhun
Abstract: Understanding the geophysical properties of hydrate-bearing sediments is critical for hydrate utilization such as prediction of hydrate distribution and concentration, as well as safety evaluation during hydrate production. Here, a customized resonant column is employed to test tetrahydrofuran (THF) hydrate-bearing sandy specimens. The results show that wave velocities of all tested specimens increase exponentially with increasing effective confining stress ( V = α × σ β ), whereas wave velocity evolution becomes almost stress-independent when critical hydrate saturation ( S h > 0.53 in this study) is reached, which transforms the hydrate morphology from non-cementing to cementing type. In addition, regardless of structure differences between tested specimens, an increased α factor and decreased β exponent follows a uniform equation β = 0.61 – 0.2 log[ α /(m/s)]. Measured wave velocity differences between hydrate-bearing and hydrate-free specimens confirm the coexistence of various hydrate morphologies based on matching results of theoretical predictions from rock physics models and interpretation of volumetric proportions of hydrates with different morphologies in tested specimens. Wave attenuation of tested specimens generally decreases with increasing effective confining stress and increase with increasing hydrate saturation. The relationship between wave attenuation and hydrate saturation ( Q S −1 = 0.015 + 0.17 S h ) is confirmed to be a hydrate saturation indicator. Considering data from field seismic surveys, this type of monotonous relationship appears to be less sensitive for hydrate morphology. Nevertheless, through the combined interpretation of wave velocities and attenuations, it is theoretically feasible to not only predict hydrate saturation, but also illustrate the evolution of hydrate morphology. Our study contributes to a better understanding of stress-related geophysical properties of hydrate-bearing sediments, which can be useful for the characterization of hydrate reservoirs. Highlights: Stress sensitive constants of wave velocities between hydrate-bearing specimens can be described by a uniform equation. Various hydrate morphologies can co-exist in synthetic specimens, and generally change with hydrate formation. Wave attenuation is confirmed to be a hydrate saturation indicator based on the laboratory tests and field seismic surveys.